Prevalence and Risk Factors of CoronaVac Side Effects: An Independent Cross-Sectional Study among Healthcare Workers in Turkey - Riad, Abanoub; Sağıroğlu, Derya; Üstün, Batuhan; Pokorná, Andrea; Klugarová, Jitka; Attia, Sameh; Klugar, Miloslav (Journal of clinical medicine, 2021)
BACKGROUND: COVID-19 vaccine hesitancy is a serious threat to mass vaccination strategies that need to be accelerated currently in order to achieve a substantial level of community immunity. Independent (non-sponsored) studies have a great potential to enhance public confidence in vaccines and accelerate their uptake process. METHODS: A nationwide cross-sectional study for the side effects (SE) of CoronaVac was carried out in February 2021 among Turkish healthcare workers who were recently vaccinated. The questionnaire inquired about local and systemic SEs that occurred in the short-term, within four weeks, following vaccination. RESULTS: A total of 780 healthcare workers were included in this study; 62.5% of them experienced at least one SE. Injection site pain (41.5%) was the most common local SE, while fatigue (23.6%), headache (18.7%), muscle pain (11.2%) and joint pain (5.9%) were the common systemic SEs. Female healthcare workers (67.9%) were significantly more affected by local and systemic SEs than male colleagues (51.4%). Younger age, previous infection, and compromised health status (chronic illnesses and regular medicines uptake) can be associated with an increased risk of CoronaVac SEs; Conclusions: The independent research shows a higher prevalence of CoronaVac SEs than what is reported by phase I-III clinical trials. In general, the results of this study confirm the overall safety of CoronaVac and suggest potential risk factors for its SEs. Gender-based differences and SEs distribution among age groups are worth further investigation.
Keywords: drug-related side effects and adverse reactions; Turkey; prevalence; CoronaVac; mass vaccination; COVID-19; health personnel